An Analysis of Teachers’ Beliefs toward Authentic Materials in Teaching Listening - Berlinda Mandasari (Universitas Teknokrat Indonesia, 2016)
This research concerns on the study of analyzing teachers’ beliefs toward authentic materials in teaching listening. This issue becomes important to analyze because teachers’ beliefs containing conceptions, world views, and mental models about the materials will shape learning and teaching practices. The subject of this research was two English teachers who specifically teach listening skill by using authentic materials in Surakarta. The data were collected through observation, questionnaire and interview and were analyzed by using interactive model proposed by Miles and Huberman. The result of this research is teachers believe that :a) authentic materials are materials produced by a native speaker of the target language not for a teaching purpose, b) authentic materials must introduce English in the real context used by the native speaker, improve students’ knowledge, Improve students’ English competence in both spoken and written, improve students’ vocabulary, introduce the culture of native speaker, improve students’ listening ability, motivate students to learn, motivate students to learn autonomously, c) authentic materials are important to use since it is motivating students and providing some aspect of English that students can learn, d) authentic materials are considered to be carefully selected before being taught to the students, e) song attracts students’ interest. The result implies that teachers’ concept toward authentic materials has shape their belief.